2010
DOI: 10.4049/jimmunol.1000432
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Specific for ImmunodominantTrans-Sialidase Epitopes Contribute to Control ofTrypanosoma cruziInfection but Are Not Required for Resistance

Abstract: CD8+ T cells are essential for controlling Trypanosoma cruzi infection. During Brazil strain infection, C57BL/6 mice expand parasite-specific CD8+ T cells recognizing the dominant TSKB20 (ANYKFTLV) and subdominant TSKB74 (VNYDFTLV) trans-sialidase gene (TS)-encoded epitopes with up to 40% of all CD8+ T cells specific for these epitopes. Although this is one of the largest immunodominant T cell responses described for any infection, most mice fail to clear T. cruzi and subsequently develop chronic disease. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 68 publications
2
75
0
Order By: Relevance
“…), and parasitic (Toxoplasma gondii and Trypanosoma cruzi) infections, there is a delay in the generation of the CD8 + T cell immune response. In addition, Ag-specific T cells become dysfunctional, express inhibitory receptors, and even fail to control the infection (57)(58)(59)(60)(61)(62)(63)(64). Although this process was initially described for models of chronic viral infections, such as lymphocytic choriomeningitis, HIV, simian immunodeficiency, and HBV and HCV (12), recent studies have shown that this phenomenon also occurs in protozoan infections (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…), and parasitic (Toxoplasma gondii and Trypanosoma cruzi) infections, there is a delay in the generation of the CD8 + T cell immune response. In addition, Ag-specific T cells become dysfunctional, express inhibitory receptors, and even fail to control the infection (57)(58)(59)(60)(61)(62)(63)(64). Although this process was initially described for models of chronic viral infections, such as lymphocytic choriomeningitis, HIV, simian immunodeficiency, and HBV and HCV (12), recent studies have shown that this phenomenon also occurs in protozoan infections (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Rosenberg et al utilized a highdose peptide tolerization approach to specifically suppress the induction of CD8 ϩ T cells of defined specificity during Trypanosoma infection (31). Mice tolerized against two immunodominant epitopes experienced a transient increase in parasite load, indicating that the protective CD8 ϩ T cell response was weakened.…”
Section: Cd8mentioning
confidence: 99%
“…50 Importantly, mice tolerized for these dominant epitopes are still able to control acute T. cruzi infection through the activation of CD8 + T cells specific for unknown alternate epitopes. 51 Identifying these epitopes may thus lead to additional vaccine antigens that could complement trans-sialidase proteins.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%